Quality Characteristics of Tilapia Crackers Made with Sago Flour as Basic Ingredient - Novia Hasyim; Lukman Mile; Nikmawatisusanti Yusuf (The NIKe Journal, 2019)
This study aims to determine the characteristics of the formula selected and crackers made from corn starch with the addition of tilapia (Oreochromis niloticus). Treatment factors in this study were different concentrations of tilapia were 30%, 50% and 70%. At the formulation stage conducted organoleptic tests (hedonic) against crackers consisting of texture, taste, color, appearance, and aroma. Phase characterization analyzed are the organoleptic quality of hedonic include texture, flavor, appearance and aroma. Hedonic test results indicate that the selected product is a composition of formula B with 100% corn starch and 50% of tilapia. Kruskal Wallis test results showed that the addition of tilapia no significant effect on the texture and flavor, but significant effect (p